Monitoring Human Neutrophil Differentiation by Digital Holographic Microscopy - do R. B. F. Lima, Maria Augusta; Cojoc, Dan (Frontiers in Physics, 2021)
We report on the usefulness of digital holographic microscopy (DHM) for the assessment of human neutrophil differentiation from myeloid cells. The cell and nuclear regions have been designated by image segmentation of the optical phase function, and the changes of the cell nucleus morphology in relation to the whole cell morphology have been examined during the process of granulocytic differentiation into mature neutrophils in PLB-985 cell line. Nucleus phase volume and circularity and the ratios between the nucleus and the cell projected area and volume provide a reliable set of parameters to characterize the maturation process. As control, cell differentiation has been monitored in parallel using standard nucleus staining and fluorescence imaging. From this research, it emerged that DHM can be used as a valid label-free solution, alternatively to the standard staining technology.